2018
DOI: 10.21894/jopr.2018.0058
|View full text |Cite
|
Sign up to set email alerts
|

Total Phenolic Contents and Antioxidant Activity of Palm Oils and Palm Kernel Oils at Various Refining Processes

Abstract: Oil palm is one of the richest sources of antioxidants such as carotenoids, tocopherols, tocotrienols and phenolic compounds. This study quantified the amount of total phenolic content (TPC) and the antioxidant activity of crude to refined palm oil and palm kernel oil products obtained from palm oil mills. The TPC of the oil extracts was determined using Folin-Ciocalteau method expressed as gallic acid equivalent (GAE). Aqueous oil extraction with methanolic solvent was efficient and extract from crude palm oi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 32 publications
0
19
1
Order By: Relevance
“…Abdullah et al found that the amount of total phenolic content in palm oil was reduced along the various stages of the refining steps, probably due to losses through absorption by bleaching earth, volatilization and degradation during the refining process. [24] Khrapova et al determined the antioxidant activity of CO and PO with chemiluminescent method. The results showed that the concentration of natural antioxidants of CO was 41.6 mg/mL, which was higher than 25.6 mg/mL of PO.…”
Section: Resultsmentioning
confidence: 99%
“…Abdullah et al found that the amount of total phenolic content in palm oil was reduced along the various stages of the refining steps, probably due to losses through absorption by bleaching earth, volatilization and degradation during the refining process. [24] Khrapova et al determined the antioxidant activity of CO and PO with chemiluminescent method. The results showed that the concentration of natural antioxidants of CO was 41.6 mg/mL, which was higher than 25.6 mg/mL of PO.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is much less frequently used due to its low stability and sensoric qualities. Conversely, the refined palm oil has considerably lower phenolic content and antioxidant capacity (Abdullah et al., 2018). The liquid fraction of refined palm oil, that is palm olein, contains approximately 40% of palmitic acid and is used mostly for frying.…”
Section: Resultsmentioning
confidence: 99%
“…However, this increment is not significant because the calculated P-value of both samples was greater than 0.05 (P > 0.05). The reason for this occurrence was based on the ethanol base oleoresins extraction as it did not contain free water (Abdullah et al, 2018). Insoluble impurities of SFO as the same as VCO samples (0.05 ± 0.01%) and the p value of all samples were higher than 0.05 (P > 0.05) after one week of storage.…”
Section: Discussionmentioning
confidence: 97%